A simple strategy to solve complicated square root problem in DTC for FPGA implementation - Jidin , Auzani (2010)
This paper presents a digit-by-digit calculation method to calculate the complicated square root problem faced in implementing the direct torque control (DTC) of induction motor drives using Field Programmable Gate Arrays (FPGA). The main principle of the proposed method is based on a two-bit shifter and a subtractor-multiplexor operation that gives simpler implementation and faster calculation. The proposed strategy was successfully implemented on an FPGA device using unsigned 32 bit and 64-bit binary square root. The strategy can be easily expanded to larger number.